MDII Scoring Dashboard (version 1.00): a tool for visualizing digital inclusiveness and innovation performance - Nisansa, Vinuri; Martins, Carolina Iglésias; Opola, Felix Ouko; Roberto, C.; Garcia Andarcia, Mariangel (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
The MDII scoring dashboard was developed as part of a set of tools to assess the social inclusiveness of digital innovations across food, land, and water systems. This tool provides decision-makers with interactive visualizations and key metrics such as accessibility, user engagement, and cultural sensitivity. The dashboard, shaped by collaborative workshops and feedback, incorporates metadata indicators, feedback mechanisms, and customizable data views for portfolio managers. By integrating both quantitative and qualitative data, it allows for monitoring performance, identifying gaps, and aligning digital tools with inclusiveness goals, supporting adaptive learning and sustainability in digital innovations.